Akhil Sharma Against Mysticism: the Unconscious Body - Edgar Tello (Universitat Autònoma de Barcelona, 2018)
This article deals with Akhil Sharma’s latest work, Family Life (2014), where Birju’s dead body, after a pool accident, shows the possibility of living after mental death. This work analyses the different therapies doctors, gurus, and spiritual leaders try upon his body, while his sorrowful mother and his alcoholic father are least able to bear them: the family cannot afford the cost of American clinics and specialists either. This criticism was also shown in Akhil Sharma’s previous novel, An Obedient Father (2000), where moral and political corruption invades all strata of life in India. In the end, the farce of mysticism becomes evident.   I relate this family life with some classical theories from Hindu tradition (Veda, Brahmana, Upanisads), and with other Western traditions (compassion and nihilism, in J.C. Mèlich, and R. Ávila’s works). I conclude by asserting that, according to these novels, it is egotistical illusion, instead of mysticism, which sheds a light upon political or social bodies.